Roles of Human Resource Managers: Indispensable in Leading to Progression of Human Resources and Organizations - Dr. Radhika Kapur, (Indian Journal of Management and Language (IJML), 2025)
Within all types of organizations, human resource managers are vested with the authority and responsibility of putting into operation all the factors, which are facilitating in upgradation of human resources. They guide and lead the human resources in the right direction. Furthermore, assistance is provided to them in leading to up-gradation of their competencies, abilities and aptitude. These need to be utilized in an effective manner in doing well in one’s job duties and achieving desired goals and objectives. One of the important aspects that needs to be taken into account is, progression is facilitated, when human resource managers and human resources are developing mutual understanding with each other. Furthermore, one will be able to render an important contribution in meeting the expectations of individuals in leadership positions. The human resource managers throughout their jobs need to be well-informed in terms of their job duties and responsibilities. Furthermore, they need to augment information in terms of various types of methodologies and procedures to generate desired outcomes. In addition, inculcation of traits of morality, ethics, diligence and conscientiousness are facilitating in leading to progression. Therefore, it is wellunderstood, roles of human resource managers are indispensable in leading to progression of human resources and organizations. The main concepts that are taken into account in this research paper are, objectives of human resource managers, understanding roles of human resource managers, and measures to be implemented in leading to up-gradation of roles by human resource managers.